PENGARUH UJI KELAYAKAN DAN SERTIFIKASI TEMPUR AMFIBI TERHADAP KESELAMATAN PERSONEL DAN MATERIEL KORPS MARINIR - Sri Wisnu Wardono; Trianggo Budhi Sukarso; Edi Iwan Bangun (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
TNI is the main component of national defense which is tasked with implementing state defense policies in order to maintain state sovereignty and the territorial integrity of the Unitary State of the Republic of Indonesia (NKRI). In order to realize the achievement of its duties, the Indonesian Navy requires adequate facilities in the form of the main weapon system (Alutsista). Marines as a component subsystem of the Integrated Fleet Weapon System (SSAT), are required to have high and reliable operational readiness capabilities. The success of the Marine Corps in carrying out its duties is largely determined by the units under it. One of them is the Cavalry Regiment which has an important role to support the main tasks of the Marine Corps, therefore the Cavalry Regiment's ability is needed in fostering and preparing the operational readiness of Cavalry elements both personnel and material in order to carry out Military Operations for War (OMP) and Military Operations. Apart from War (OMSP). In carrying out its duties, functions and roles, both as a unit that operates and maintains the operational readiness of amphibious lander combat vehicles. Before carrying out the Tempur Exercise, it is tested for feasibility and certification tests in order to minimize the occurrence of accidents. This study to see the effect of airworthiness testing and certification on the safety of Marine Corps personnel and materials with quantitative methods and data processing with the SPSS 25 program. Non-Probability Sampling the sampling technique used is incidental sampling. 237. The results of this study are that there is a positive and significant effect between the feasibility test on the safety of personnel and materials with of 3.417 and a t-table of 1.970, there is a positive and significant effect between certification on the safety of personnel and materials with 6.219 and t-table 1.970, there are positive and significant influence between the simultaneous feasibility test and certification on the safety of personnel and material with 118.249 and f-table 0.051. The value of the correlation coefficient is 0.709 which is declared strong or 70.9% and the value of R2 = 0.50.3 which means that it is 50.3% while the remaining 49.7% is influenced by other variables outside the model studied.